Transcendental Logarithmic Production Frontiers - Christensen, Laurits R.; Jorgenson, Dale W.; Lau, Lawrence J. (The Review of Economics and Statistics, 1973)
Focuses on additive and homogeneous production possibility frontiers that have played an important role in formulating statistical tests of the theory of production. Characterization of the class of production possibility frontiers that are homogenous and additive; Representation of the production possibility frontier; Statistical tests of the theory of production. (Из Ebsco)